Botulinum Toxin Therapy Manual for Dystonia and Spasticity - Rosales, Raymond L.; Dressler, Dirk (IntechOpen, 2016)
Taking exception from previous publications and reviews, this handbook boldly knits botulinum toxin therapy indications in both dystonia and spasticity. Botulinum toxin therapy has indeed withstood the test of time in terms of its efficacy and safety, as applied in hyperfunctional states of the muscle and exocrine glands. Topics were chosen spanning from the basic science to the clinical applications and to instrument-guidance injections. The format was envisioned to be timely as one (either a novice or an experienced clinician) applies practical approaches with botulinum toxin therapy ranging from straightforward to challenging clinical scenarios. As well, clinicians and students alike will find the book useful in content and relevance to contemporary times. Please read with no fear and don't doubt because indeed you eventually become the winner as you finish the book.